Social comparison and risk taking behavior - Astrid Gamba; Elena Manzoni; Luca Stanca (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
This paper studies the effects of social comparison on risk taking be- havior. In our framework, decision makers evaluate the consequences of their choices as changes with respect to both their own and their peers' conditions. We test experimentally whether different positions in the social ranking determine different risk attitudes. Subjects interact in a simulated workplace environment, where they receive possibly different wages as compensation for effort and then undertake a risky decision that may give them an extra gain. We find that social comparison matters for risk attitudes. In addition, risk aversion decreases with the size of social gains. As a consequence, subjects are less risk averse in social loss than in small social gain, whereas their risk attitudes do not differ between social loss and large social gain.
Keywords: C91; D0; D81; 330; interdependent preferences; reference point; risk aversion; social comparison